P181cAMP-mediated Rac1 activation regulates the re-establishment of endothelial adherens junctions and barrier restoration during inflammation. (15th July 2014) - Aslam, M; Nef, H; Troidl, C; Schulz, R; Noll, T; Hamm, C; Guenduez, D
Abstract: Background: Inflammatory mediators like thrombin and TNFα disrupt endothelial junctions and barrier integrity, leading to edema formation. This increase in endothelial permeability is followed by slow restoration of the endothelial barrier, which is critical for the maintenance of basal endothelial permeability. However, the molecular mechanism of recovery of the endothelial barrier in response to inflammatory mediators has not yet been well delineated. The aim of the present study was to explore the mechanism of this barrier restoration. Specific emphasis was given to the role of Rac1 GTPase activation, which is an important regulator of endothelial adherens junction (AJ) integrity. Methods: The study was carried out on cultured human umbilical vein endothelial cells (HUVEC). Endothelial barrier function was analyzed by measuring the flux of trypan blue-labeled albumin and immunostaining of AJ by confocal microscopy. The level of cellular cAMP was measured by ELISA and Rac1 GTPase activity was determined by pull-down assay. Results: Exposure of HUVEC monolayers to thrombin caused a 5-fold increase in endothelial permeability withing 10 min followed by slow recovery during the next 2 h. The cellular cAMP content dropped to 30% of the basal level after 10 min of thrombin treatment; thereafter, this slowly increased to a 3-fold higher level after 60 min of thrombin treatment. Likewise, Rac1 GTPase activity dropped by 70% after 10 min and increased by 250% after 60 min of thrombin treatment. Inhibition of Rac1 activity using a specific pharmacological inhibitor (NSC23766; 50 μM) abrogated the barrier resealing process, suggesting a Rac1-dependent phenomenon. Similarly, inhibition of either adenylyl cyclase (MDL12; 100 nM) or its downstream targets PKA and Epac (PKI [10 μM] and ESI009 [1 μM], respectively) abrogated Rac1 activation and completely blocked barrier recovery and resealing of endothelial AJ. Conclusion: The data of the present study demonstrate that endothelial barrier recovery is regulated by Rac1 GTPase activation. This activation, due to increased levels of cellular cAMP, enhances the relocalisation of AJ components to cell-cell junctions and thus mediates barrier restoration.